(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Computational Fluid Dynamics (CFD) is the analysis of fluid behaviour employing numerical solution methods. Using CFD it is possible to analyse simple and complex fluid-gas, fluid-fluid or fluid-solid interactions. Fluid dynamics is described with laws of physics in the form of partial differential equations also known as Navier-Stokes equations. Sophisticated CFD solvers transform these laws into algebraic equations which are solved by numerical methods. In this paper Ansys CFX and Fluent analysis systems as research methods are used to visualize flow patterns in a stirred tank bioreactor. The results obtained are informative and can be used to improve the yield of biomass. CFD analysis can save time and aid fluid system designing process. This approach is cheaper and faster compared to conventional build-and-test process. However, it should be noted that CFD analysis results are as accurate as the level of skill possessed by a CFD engineer therefore there are still place for hands-on testing. Authors have developed a stirred tank model and visualized flow patterns. The research presents experimental computation methods and the model setup key parameters. The developed model allows to predict flow patterns inside stirred systems and evaluate efficiency of the mixing process by analysing parameters such as velocity field, turbulence eddy frequency, shear strain rate and power input.